2014
DOI: 10.1371/journal.pone.0090715
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Fibroblasts Display a Non-Fibrotic Phenotype Distinct from Skin Fibroblasts in Three-Dimensional Cultures

Abstract: Scar formation following skin injury can be a major psychosocial and physiological problem. However, the mechanisms of scar formation are still not completely understood. Previous studies have shown that wound healing in oral mucosa is faster, associates with a reduced inflammatory response and results to significantly reduced scar formation compared with skin wounds. In the present study, we hypothesized that oral mucosal fibroblasts from human gingiva are inherently distinct from fibroblasts from breast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 71 publications
(110 reference statements)
1
97
0
4
Order By: Relevance
“…They also contain elevated levels of immunomodulatory and anti-fibrotic TGF-b3 relative to pro-fibrotic TGF-b1 as compared with similar skin wounds (13,36,39,40,49,50). Interestingly, accumulating evidence has suggested that the gingival wound-healing response may also depend on a distinct phenotype of gingival fibroblasts (11,13,38,51). Are gingival fibroblasts different from other oral fibroblasts?…”
Section: Specific Features Of Gingiva In Vivomentioning
confidence: 99%
See 3 more Smart Citations
“…They also contain elevated levels of immunomodulatory and anti-fibrotic TGF-b3 relative to pro-fibrotic TGF-b1 as compared with similar skin wounds (13,36,39,40,49,50). Interestingly, accumulating evidence has suggested that the gingival wound-healing response may also depend on a distinct phenotype of gingival fibroblasts (11,13,38,51). Are gingival fibroblasts different from other oral fibroblasts?…”
Section: Specific Features Of Gingiva In Vivomentioning
confidence: 99%
“…The findings showed that gingival fibroblasts are programmed for fast resolution of inflammation, ECM remodeling and angiogenesis conducive for fast and scarless wound healing. In contrast, skin fibroblasts are prone to abundant ECM deposition, active TGF-b signaling and contractility, characteristics of fibrosis and scar formation (51). Thus, gingival fibroblasts may provide an advantage over skin fibroblasts in therapeutic modalities aiming to promote fast and scarless wound healing.…”
Section: Developmental Origin and Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that decreased TGF-β signaling and consequent reduced levels of connective tissue growth factor (CTGF) may be responsible for the progressive loss of collagen in the aged skin (Quan et al 2010). Although TGF-β regulation may differ in skin versus gingival cells (Mah et al 2014), it is plausible that gingival cells may experience changes in their response to TGF-β during aging. Collagen fibers are significantly modified and reorganized during the slow tissue-remodeling process in which molecules change their general orientation.…”
Section: Tissue Remodelingmentioning
confidence: 99%